Early Christians speak : faith and life in the first three centuries - Ferguson, Everett (ACU Press, 1999)
These studies in early church history cover various aspects of the church life of early Christians. They focus on the second century. What did the second century Christian leaders say about faith, baptism, infant baptism, worship services, the Lord's Supper, prayer, singing, church organization, mercy and the role of women? New Testament texts bearing on the topic are listed at the beginning of each chapter. We are talking about the same community of people, the same church, as existed in the New Testament. Such writings have an important bearing on the interpretation of the Scriptures.